1994
DOI: 10.1111/j.1472-8206.1994.tb00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐induced parkinsonism: a review

Abstract: The main clinical features, pathophysiology and underlying mechanisms of drug-induced parkinsonism are reviewed. The clinical manifestations of drug-induced parkinsonism are often indistinguishable from idiopathic Parkinson's disease. However, some subtle differences may exist: for example drug-induced parkinsonism is often associated with tardive dyskinesias, bilateral symptoms and the absence of resting tremor, etc. Besides toxins (eg manganese, carbon monoxide or MPTP), many drugs are known to produce parki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(38 citation statements)
references
References 108 publications
1
36
1
Order By: Relevance
“…In addition, gender-related differences are a common feature of the pharmacological properties of most centrally active drugs (19)(20)(21); for instance, drug-induced parkinsonism in humans exhibits a femaleto-male predominance ratio of about 2:1 (22). Nevertheless, there is no information concerning gender dimorphism in the effects of nitrergic agents on the phenomenon of neuroleptic-induced catalepsy.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, gender-related differences are a common feature of the pharmacological properties of most centrally active drugs (19)(20)(21); for instance, drug-induced parkinsonism in humans exhibits a femaleto-male predominance ratio of about 2:1 (22). Nevertheless, there is no information concerning gender dimorphism in the effects of nitrergic agents on the phenomenon of neuroleptic-induced catalepsy.…”
Section: Introductionmentioning
confidence: 98%
“…Drug-induced parkinsonism (DIP) is a common movement disorder [5] caused by drugs affecting dopamine receptors [6][7][8]. While TMZ was found to be generally well tolerated in clinical trials, a number of recent studies have reported parkinsonism symptoms and exacerbation of Parkinson's disease as adverse drug reactions related to treatment with TMZ.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, drug-induced parkinsonism is frequently indistinguishable from idiopathic parkinsonism [8]. Several cases have been described where drug-induced parkinsonism first appears and subsequently idiopathic parkinsonism is diagnosed [9].…”
Section: Importance Of the Husband-wife Concordance Of Pdmentioning
confidence: 99%